Isocaloric swine finishing diets with various percentages of alfalfa meal and tallow - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Increasing the alfalfa meal to 30% in a finishing pig diet did not significantly reduce average daily gain when tallow was also added to maintain the caloric density of the ration. Digestibility of dry matter and gross energy were reduced as fiber increased, but feed efficiency was not significantly changed with caloric density maintained. Increasing dietary alfalfa meal and tallow content did not change the percentage of dietary nitrogen retained. Rations containing high levels of alfalfa meal and tallow tended to "bridge" in self-feeders.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Isocaloric; Alfalfa meal; Tallow